How Hard do Women Climb the Ladder? - Mohamed Yunos, Rahimah; Ahmad, Syahrul Ahmar (Archives of Business Research, 2023)
This paper reviews the literature on the glass ceiling and glass cliffs relating to female career enhancement. Two theories relevant to the issue are highlighted and four relevant issues on the predicament of female employees being promoted to the management level are presented. First, the rate of female employees promoted to a higher management position is far below than men. Second, factors that impede their career enhancement vary from personal to the organizational level. Third, women who break the glass ceiling face challenges as a leader. Fourth, this paper reviews the literature on what employers and female individuals could do to improve the situation.